Progressive attraction: on the use and grammaticalization of progressive aspect in Dutch, Norwegian, and German - Behrens, Bergljot; Flecken, Monique; Carroll, Mary (Journal of Germanic linguistics, 2013)
This paper investigates the use of aspectual constructions in Dutch, Norwegian, and German, languages in which aspect marking that presents events explicitly as ongoing, is optional. Data were elicited under similar conditions with native speakers in the three countries. We show that while German speakers make insignificant use of aspectual constructions, usage patterns in Norwegian and Dutch present an interesting case of overlap, as well as differences, with respect to a set of factors that attract or constrain the use of different constructions. The results indicate that aspect marking is grammaticalizing in Dutch, but there are no clear signs of a similar process in Norwegian.*